Spirals of Speaking Out? Effects of the "Suppressed Voice Rhetoric" on Audiences' Willingness to Express Their Opinion. Issue 3 (2nd July 2020) - Kunst, Marlene; Toepfl, Florian; Dogruel, Leyla
ABSTRACT: A defining feature of counterpublics is to claim that their views are deliberately excluded from the mainstream public sphere. This rhetorical strategy – which we theorize as "suppressed voice rhetoric" (SVR) – has become omnipresent in today's polarized media environments. In this article, we present an experimental study (N = 464) that investigated the effect of SVR in right-wing counterpublic user comments on the audience. We found that, when exposed to comments with SVR, participants with low media trust became more eager to express their opinion. This effect may contribute to setting in motion a "spiral of speaking out" among media-distrusting individuals.